Changing citizenship norms among adolescents, 1999-2009-2016: A two-step latent class approach with measurement equivalence testing - Oser, Jennifer; Hooghe, Marc; Bakk, Zsuzsa; Di Mari, Roberto (Quality & quantity, 2023)
The evolution of citizenship norms is considered a driving force behind changing political processes in contemporary democracies. Competing expectations have emerged on this topic: a ‘citizen engagement’ argument anticipates an increase in norms that emphasize engaged and expressive values, while a ‘democratic erosion’ argument expects an increase in traditional and even authoritarian values. With a theoretical focus on individual-level citizenship norms, we analyze uniquely high-quality cross-national data on adolescents in 14 diverse countries in 1999, 2009 and 2016. We integrate recently developed innovations in latent class analysis that have not yet been implemented in applied research by using a two-step estimator for multilevel latent class models with measurement equivalence testing. The findings confirm expectations of the existence of both ‘engaged’ and ‘duty-based’ citizenship norms, but the stability in the prevalence of these norms contrasts expectations in the literature. The findings also identify additional normative types that do change in prevalence over time—namely, decreased prevalence of a ‘mainstream’ norm that parallels mean societal scores, along with increased prevalence of both a ‘maximalist’ high-scoring group and a ‘subject’ low-scoring group. The results regarding over-time change provide partial support for both the citizen engagement and democratic erosion arguments, and highlight the importance of robust measurement of these concepts to contribute to the debate of evolving global trends in citizenship norms. We conclude by discussing how the multilevel latent class modeling approach used in this article can be applied to related topics to better understand changing relationships between citizens and democratic systems.